#TITLE_ALTERNATIVE# - KURNIA WIBOWO (NIM : 15109014) ; Pembimbing I : Prof. Ir. Ketut Wikantika, M.Eng., Ph.D., CLORINDA
Water scarcity is increasingly becoming a problem highlighted in the agricultural world in Indonesia . The number of crop failures caused by the irrigation system which is not effective and efficient. Actual evapotranspiration becomes a key determinant in predicting crop water requirements. Monitoring daily and seasonal actual evapotranspiration can give rigorous value of the water consumption of the agricultural area. The method used in determining the daily and seasonal actual evapotranspiration is SEBAL (Surface Energy Balance Alogarithm on Land). This method utilizes remote sensing technology combined with weather data field observations. MODIS land products acquired in eight dates between May to September 2012 are used in this study. Study area are 23 tea plantations located in West Java, Indonesia. From the results of this study, the average value of actual evapotranspiration in the eight dates is 2,86 mm/day with a standard deviation of Ã‚Â±0,99 mm/day. Although the value needs further verification, SEBAL method is logically able to describe spatial variability of actual evapotranspiration. The result of sensitivity analysis shows a close correlation between SEBAL-based actual evapotranspiration with parameters of sensible heat flux and land surface temperature.